Resonant BLDC Motor Drive System for Medical Applications - Vidhya, C.; Ravikumar, V.; Muralidharan, S. (Current Signal Transduction Therapy, 2021)
Aims: The work aims to implement a soft switched high frequency ac link universal power converter controlled BLDC motor for medical applications. The universal power converter is an ac link converter, with the parallel combination of an inductor and a capacitor which offers improved power factor, low power consumption and more efficiency. Materials and Methods: SVPWM technique is utilized as a control technique for the proposed converter. AC link converter controlled with PDM technique requires an additional control procedure or an algorithm for regulating the output power of the PDM converters. SVPWM technique was adopted to turn ON and OFF the input and output switches in sequence to get the regulated power at the output. Result and Conclusion: These types of inverters could be used in medical field as an alternate to conventional inverters during power shut downs. The inverter proposed in this work has both the capability to step up and step down the input voltage based on the load requirements. The soft switched AC link inverter may be incorporated in a variety of applications including medial applications, industrial needs, renewable energy resources, variable frequency drives and electric and hybrid vehicles.
Keywords: space vector pulse width modulation